Principles Of Enviromental Science: Inquiry and Applications - William P.Cunningham, Mary Ann Cunningham (McGraw Hill, 2006)
This book provides a solid foundation in scientific approaches to enviromental problems and solutions. We integrate information from a wide range of disciplines from both of natural and social sciences